Biallelic Missense Mutation in the ECEL1 Underlies Distal Arthrogryposis Type 5 (DA5D) - Umair, Muhammad; Khan, Amjad; Hayat, Amir; Abbas, Safdar; Asiri, Abdulaziz; Younus, Muhammad; Amin, Wajid; Nawaz, Shoaib; Khan, Shazia; Malik, Erum; Alfadhel, Majid; Ahmad, Farooq (Frontiers in Pediatrics, 2019)
Distal arthrogryposis (DA) is a heterogeneous sub-group of arthrogryposis multiplex congenita (AMC), mostly characterized by having congenital contractures affecting hands, wrists, feet, and ankles. Distal arthrogryposis is mostly autosomal dominantly inherited, while only one sub-type DA type 5D is inherited in an autosomal recessive manner. Clinically, DA5D is described as having knee extension contractures, micrognathia, distal joint contractures, clubfoot, ptosis, contractures (shoulders, elbows, and wrists) and scoliosis. Using whole exome sequencing followed by Sanger sequencing, we report on a first familial case of DA5D from Pakistani population having a novel biallelic missense mutation (c.158C>A, p.Pro53Leu) in the ECEL1 gene. Our results support that homozygous mutations in ECEL1 causes DA5D and expands the clinical and allelic spectrum of ECEL1 related contracture syndromes.